2022
DOI: 10.21303/2313-8416.2022.002320
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the high murder rate in South Africa

Abstract: The objects of this research are: first, to explain some of the causes of high murder rates in South Africa. Second, to refute the labelling of South Africa as the murder capital of the world. Third, exploring some alternative ways to violence resulting in deaths. The author investigated the following problems: murder done predominately by men, the inefficiency or shortcomings of the police to investigate murder successfully and lack of reports showing a drastic reduction of murders rates, possible due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In terms of income distribution, South Africa is one of the most unequal countries in the world. A society without Nordic-style decommodification of life chances places extensive pressure on socially disadvantaged persons to maintain or improve their position in the social hierarchy (Yesufu, 2022). The high risk of men committing violent crimes has been interpreted as a means for them to achieve social mobility, belonging, and respect and establish street credibility in contexts of “advanced marginality” (Lindegaard, 2017, as cited by Lindegaard & Jacques, 2014; Wacquant, 2008).…”
Section: Homicide In Study Locationsmentioning
confidence: 99%
“…In terms of income distribution, South Africa is one of the most unequal countries in the world. A society without Nordic-style decommodification of life chances places extensive pressure on socially disadvantaged persons to maintain or improve their position in the social hierarchy (Yesufu, 2022). The high risk of men committing violent crimes has been interpreted as a means for them to achieve social mobility, belonging, and respect and establish street credibility in contexts of “advanced marginality” (Lindegaard, 2017, as cited by Lindegaard & Jacques, 2014; Wacquant, 2008).…”
Section: Homicide In Study Locationsmentioning
confidence: 99%
“…The burden of violence in South Africa is emphasised by the crime rate of 77.3%, which is the third highest crime rate in the world. 17 In the analysis of spinal fractures (196/1012), these accounted for most of the orthopaedic injuries reported on a CT pan scan. The only other study to have also shown this was published by Shannon et al 5 The authors also used CT pan scans which were compared to clinically suspected injuries.…”
Section: Referencementioning
confidence: 99%